Comparison of the Ocular Surface Disease Index and the Symptom Assessment in Dry Eye Questionnaires for Dry Eye Symptom Assessment - Raul Martin; EMO Research Group (Life, 2023)
Background: Patient-reported dry eye symptoms (DESs), assessed using the Ocular Surface Disease Index (OSDI) and the Symptom Assessment iN Dry Eye (SANDE) questionnaires, were compared in a large sample of patients. Methods: The correlation (Spearman coefficient) and agreement (Bland-Altman analysis) between the OSDI and SANDE questionnaire scores (with and without score normalization) were assessed in 1033 patients and classified according to the OSDI score as non-DES and DES in a cross-sectional analysis. Results: The normalized and non-normalized SANDE results were higher than the OSDI results in all samples (2.83 ± 12.40 (p = 0.063) and 2.85 ± 15.95 (p = 0.016), respectively) and in non-DES (p > 0.063) and DES (p < 0.001) with both OSDI cutoff values. Weak correlations were found (Spearman coefficient <0.53; p < 0.001) in all cases except DES (0.12, p = 0.126). Weak agreement was found with a Bland-Altman analysis of the normalized and non-normalized scores of both questionnaires (mean difference from −7.67 ± 29.17 (DES patients) to −1.33 ± 8.99 (non-DES patients) without score normalization, and from −9.21 ± 26.37 (DES patients) to −0.85 ± 4.01 (non-DES) with data normalization), with a statistically significant linear relationship (R2 > 0.32, p < 0.001). The SANDE questionnaire did not yield the same patient classification as OSDI. The same operative curves (ROC) of the SANDE normalized and non-normalized scores were used to differentiate among patients with DES using OSDI < 12 (0.836 ± 0.015) or OSDI < 22 (0.880 ± 0.015) cutoff values. Conclusions: Normalized and non-normalized data collected from the SANDE questionnaire showed relevant differences from those of the OSDI, which suggests that the results of the SANDE visual analog scale-based questionnaire provide different patient classifications than the OSDI score.